Parents and Daughter Relationships in Shakespeare's Romeo and Juliet - Tamba, Asima Rohana Parulian; Girsang, Martina; Sitinjak, Vivi Novalia (PT. Impola Toba Lendt, 2024)
This study is research that focuses on the relationship between parents and their daughters and the impact it has on the main female character in drama Romeo and Juliet. The analysis shows that the role of parents, especially fathers, in determining their daughter's life, including marriage matters, has a huge influence on the decision her daughter takes when she chooses the man she loves over the man her parents chose because it ended tragically. The parenting style of the parents, especially the father, at that time had changed his daughter from obedient to rebellious, even though she had to lose her life. The study conducted library research in the process of writing this thesis. The data were taken from the original version Shakespeare’s Romeo and Juliet ebook (1957), Global Grey. The theory proposed by Greenbalt (1982) with the social and cultural context approach by Long (2024) is used in analyzing what kind of the relationship between the parents and their daughter in this drama resulted in a tragedy at the end of the story. The discovery was that the very big role of a father in his daughter's life, especially in determining her life partner, had made his daughter take a very brave decision which ended tragically but everything is to late.